Takaful investment portfolios : a study of the composition of takaful funds in the GCC and Malaysia - Tolefat, Abdulrahman Khalil (Wiley finance series., 2013)
A groundbreaking study of the investment portfolios of takaful companies, their general investment patterns, and their future investments The Islamic finance industry has witnessed remarkable growth over the last decade, and one of the most successful segments-poised for even greater expansion-is the Islamic insurance (takaful) industry. In Takaful Investment Portfolios, distinguished takaful scholar Abdulrahman Khalil Tolefat explores the investment portfolios of takaful companies in both the GCC countries and Malaysia, the tip of Islamic finance industry. Investigating the trends and patterns of investment of takaful companies, the book looks at shareholders as well as general and family funds to determine where these companies are investing today, and where they are likely to invest in the future. Presenting new and novel research on the investment patterns of takaful companies, Takaful Investment Portfolios covers the history of the industry and takaful models and how they work, and presents in-depth studies of both their real-world and desired portfolio investments. Presents unique new research into the investment portfolios of takaful companies in the GCC and Malaysia Examines the gap between desired and actual investment portfolios of takaful companies Explores expected areas for future investment Groundbreaking in its depth, Takaful Investment Portfolios is an unprecedented study of the investments of takaful companies.